The Impact of Snakes and Ladders on Motor and Cognitive Development in Children: A Systematic Literature Review - Pradiansyah, Kevin Septia; Rhousnaka , Dika; Fahliza, Aqshal Ilham; Marliany, Heni; Sukmawati, Ima; Rahayu, Yuyun (Inspirasi Foundation, 2025)
Introduction: Educational games are instrumental in supporting early childhood development, particularly in enhancing motor and cognitive abilities. Snakes and Ladders is a commonly used game that promotes strategic thinking, coordination, and social interaction.Objective: This study aims to systematically analyze and synthesize research findings related to the impact of Snakes and Ladders on children’s motor and cognitive development. Specifically, it evaluates outcomes in number comprehension, memory retention, strategic thinking, fine motor skills, and hand-eye coordination. Methods: A systematic search was conducted in PubMed, ProQuest, Garuda, and JSTOR for studies published between 2020 and 2025. Eligible studies included children aged 4–6 years, utilized Snakes and Ladders as an intervention, and reported outcomes related to motor and cognitive development. Data extraction and quality assessment were independently performed by three reviewers using the PRISMA Flow Diagram and CAST Checklist. Results: Six studies involving a total of 89 participants met the inclusion criteria. Findings indicate that Snakes and Ladders significantly improves both motor and cognitive outcomes in early childhood. Following two cycles of intervention, the proportion of children meeting motor development benchmarks increased from 37% to 86%. Cognitive development also improved, with average scores rising from 7.4 to 13 after four weeks. The percentage of children categorized as highly developed increased from 20% to 47%, and 72% achieved expected developmental milestones after six weeks. Conclusion: The Snakes and Ladders game is an effective educational tool for enhancing motor and cognitive development in children aged 4–6 years. Integration of such games into early childhood education is recommended to support holistic development.